Generalized (ℑ, ρ, θ)-convexity and its classification for set functions - Venkateswara Reddy L.; Mukherjee R.N. (My University, 2025)
The present paper aims at giving a classification for generalized (ℑ, ρ, θ)-convexity for set-functions. Direct implications of the relations existing between various types of (ℑ, ρ, θ)-convexity and generalized (ℑ, ρ, θ)-convexity are presented as well as a block diagram has been proposed which illustrates the implications reflected in the present setting.